Mitochondrial ROS modulate presynaptic plasticity in the drosophila neuromuscular junction - Irina Stavrovskaya; Bethany Kristi Morin; Stephen Madamba; Cliyahnelle Alexander; Alexis Romano; Samia Alam; Lucas Pavlov; Erna Mitaishvili; Pablo M. Peixoto (Redox Biology)
The elevated emission of reactive oxygen species (ROS) from presynaptic mitochondria is well-documented in several inflammatory and neurodegenerative diseases. However, the potential role of mitochondrial ROS in presynaptic function and plasticity remains largely understudied beyond the context of disease. Here, we investigated this potential ROS role in presynaptic function and short-term plasticity by combining optogenetics, whole cell electrophysiological recordings, and live confocal imaging using a well-established protocol for induction and measurement of synaptic potentiation in Drosophila melanogaster neuromuscular junctions (NMJ). Optogenetic induction of ROS emission from presynaptic motorneuron mitochondria expressing mitokiller red (mK) resulted in synaptic potentiation, evidenced by an increase in the frequency of spontaneous mini excitatory junction potentials. Notably, this effect was not observed in flies co-expressing catalase, a cytosolic hydrogen peroxide (H2O2) scavenging enzyme. Moreover, the increase in electrical activity did not coincide with synaptic structural changes. The absence of Wnt1/Wg release from synaptic boutons suggested involvement of alternative or non-canonical signaling pathway(s). However, in existing boutons we observed an increase in the active zone (AZ) marker Brp/Erc1, which serves as docking site for the neurotransmitter vesicle release pool. We propose the involvement of putative redox switches in AZ components as the molecular target of mitochondrial H2O2. These findings establish a novel framework for understanding the signaling role of mROS in presynaptic structural and functional plasticity, providing insights into redox-based mechanisms of neuronal communication.